2022
DOI: 10.52223/jess.20223208
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors and Job Stress among School Teachers of Punjab, Pakistan

Abstract: Job Stress is considered as the pressure and tension the employees of any organization have to face during their duties due to the unnatural demands of their job. Job stress has become such a common phenomenon that almost none can deny to get experienced it. As the teachers belong to a noble profession, i.e., the profession of the Prophets, hence the researcher, in order to determine whether they also undergo job stress, conducted this survey-based, descriptive and cross-sectional study. This study was also su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Based on the results of this study revealed that there will be greater teacher turnover intentions when their workload is high. These results matched with the study results of Mahmood et al (2022), Ekabu et al (2018), andKim (2015), which emphasized that teacher workload and competitive work environment in schools, the introduction of a new education system, lower educational resources and high expectations from society and other stakeholders are indicators that stronger than teacher turnover intentions.…”
Section: The Effect Of Teacher Workload On Teacher Turnover Intentionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on the results of this study revealed that there will be greater teacher turnover intentions when their workload is high. These results matched with the study results of Mahmood et al (2022), Ekabu et al (2018), andKim (2015), which emphasized that teacher workload and competitive work environment in schools, the introduction of a new education system, lower educational resources and high expectations from society and other stakeholders are indicators that stronger than teacher turnover intentions.…”
Section: The Effect Of Teacher Workload On Teacher Turnover Intentionsupporting
confidence: 85%
“…Based on the results, the perspective of nonpermanent teachers in public schools was found to be more inclined to transfer intentions when they were not motivated to work. This study is also confirmed by the research of Kim (2015), Grant et al (2017), andMahmood et al (2022), which concluded that the intrinsic motivation of teachers is a significant factor that reduces or triggers the intention to switch teachers from school.…”
Section: Figure 2 Validity Testing Based On Factor Loading the Effect...supporting
confidence: 78%